INFLUENCE OF FETAL SEX, PARITY AND BREAST SIZE INTRAUTERINE GROWTH - Ticona, Manuel (2015)
OBJETIVE: To determine the influence of fetal sex, parity and maternal height on intrauterine growth curve. MATERIALS AND METHODS: Prospective enrollment of newborns (RN) successive live without factors of intrauterine growth, anthropometric techniques controlled. RESULTS: Of the 8735 selected RN living in the six years studied (1995-2000), 3240 were children of primiparous, multiparous 4150, 4167 female, 4568 male. The men had average birth weight of 113-150 g higher than girls and children of multiparous exceeded 192-238 ga those of primipara, significant differences. The 5833 mothers had an average size of 155 ± 6.1 cm and were divided into three groups: 720 with larger size of 161 cm, 4411 with size between 149 and 161cm and 702 with equal or smaller size of 148 cm. The three groups had RN with directly proportional to weight and maternal height (p <0.01) size. CONCLUSIONS: Fetal sex, maternal parity and height significantly influence birth weight.